THE CORRELATION BETWEEN COGNITIVE TEST-TAKING STRATEGIES AND ACHIEVEMENT IN TOEFL READING COMPREHENSION OF THE STUDENTS OF ENGLISH DEPARTMENT AT STATE UNIVERSITY OF MAKASSAR - Sukmawati, Sukmawati (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2016)
This study investigated correlation between cognitive test-taking strategies and achievement in TOEFL reading comprehension. It was conducted to find out: (1) the most dominant cognitive test-taking strategy applied by the students of English Department at the State University of Makassar, (2) the TOEFL reading achievement of the students of  English Department at the State University of Makassar, (3) the correlation between students’ cognitive test-taking strategies and their achievement in TOEFL reading comprehension. The research applied correlation research design. This research was conducted to the fourth semester students in three fields of study at English Department of State University of Makassar. There were 20 students were from English Education, 12 students from English Literature and 15 students from Business English. The data were collected through documentation of TOEFL reading comprehension score and questionnaire. The research result showed that (1) comprehending strategy was the most dominant cognitive test-taking strategy applied by the students of English Department at the State University of Makassar, (2) the TOEFL reading achievement was achieved into fair category. It was proven by mean score 42.51 range from 21-30 score. (3) there was correlation between cognitive test-taking strategies and TOEFL reading achievement with r = .822 classified as high category in which score interval was higher than 66. Therefore, cognitive test-taking strategies have a role toward TOEFL reading achievement.